2020
DOI: 10.1007/s13394-020-00331-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of spatial, verbal, numerical, and general reasoning abilities in complex word problem solving for young female and male adults

Abstract: This study analyzed the relative importance of different cognitive abilities for solving complex mathematical word problems (CWPs)-a demanding task of high relevance for diverse fields and contexts. We investigated the effects of spatial, verbal, numerical, and general reasoning abilities as well as gender on CWP performance among N = 1282 firstyear university engineering students. Generalized linear mixed models unveiled significant unique effects of spatial ability, β = 0.284, verbal ability, β = 0.342, nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 76 publications
1
31
1
2
Order By: Relevance
“…Therefore, in Study 2, three independent measures of the spatial constructs under consideration were used. Previous research into the relationship between spatial reasoning and math have highlighted the importance of controlling for verbal skills to aid interpretation of the analysis (Mix et al, 2016;Reinhold et al, 2020); therefore, a verbal reasoning measure was included in Study 2. The SRI (Ramful et al, 2017) has no set time limit.…”
Section: Study 1: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, in Study 2, three independent measures of the spatial constructs under consideration were used. Previous research into the relationship between spatial reasoning and math have highlighted the importance of controlling for verbal skills to aid interpretation of the analysis (Mix et al, 2016;Reinhold et al, 2020); therefore, a verbal reasoning measure was included in Study 2. The SRI (Ramful et al, 2017) has no set time limit.…”
Section: Study 1: Discussionmentioning
confidence: 99%
“…Given its utility for the development of geometric reasoning, it is reasonable that MR skill is closely aligned to mathematical proficiency in the middle school years (Bruce & Hawes, 2015;Mo e, 2018). To date, MR is one of the most commonly studied forms of spatial reasoning in its connection with mathematics, with strong links to both standardized mathematics achievement (Lachance & Mazzocco, 2006;Reinhold et al, 2020;Sorby & Panther, 2020) and geometric problemsolving (Battista, 1990).…”
Section: Spatial Affordances For Different Mathematics Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Another emergent theme within theoretical considerations is the contextualization of spatial reasoning within other cognitive skills (Reinhold et al 2020), content knowledge (Fujita et al 2020), and cultural factors (Owens 2020; Sorby & Panther 2020). Using a generalized linear mixed model, Reinhold et al 2020 found that students use spatial ability, verbal ability, numerical ability, and general reasoning in solving complex word problems. Despite a male advantage on spatial and numerical ability, the relative unique contributions of the four cognitive skills remain constant across genders.…”
Section: Contributions To Theorymentioning
confidence: 99%